Diasporic cold warriors nationalist China, anticommunism, and the Philippine Chinese, 1930s-1970s - Kung, Chien-Wen 1981- (Ithaca, [New York] Cornell University Press, 2022)
"Explains how and why the Philippine Chinese became the most ardent overseas Chinese supporters of the Kuomintang during the Cold War. This book argues for a networked and diasporic understanding of the KMT-ROC party-state. Ties between the Philippine Chinese, the ROC, and the Philippines were constitutive of an intra-Asian anticommunist ecumene: a Cold War waged not by the United States and not only by states but by Asian countries and peoples working with each other"-
Introduction : The Philippine Chinese as Cold Warriors -- The KMT, Chinese Society, and Chinese Communism in the Philippines before -- A "Period of Bloody Struggle" : The Rise of the Philippine KMT, 1945-1948 -- Practicing Anticommunism : Chinese Self-Fashioning in the Cold War Philippines -- Anticommunism in Question : "Communists" and ROC-Philippine Relations in the 1950s -- Networking Ideology : Chinese Society and Transnational Anticommunism, 1954-1960 -- Experiencing the Nation : Philippine-Chinese Visits to "Free China" -- Dissent and Its Discontents : The Chinese Commercial News Affair.
Includes bibliographical references (pages 263-278) and index.
Keywords: Zhongguo guo min dang; Anti-communist movements -- China -- History -- 20th century; Anti-communist movements -- Philippines -- History -- 20th century; Anti-communist movements -- Taiwan -- History -- 20th century; Chinese -- Political activity -- Philippines -- History -- 20th century